2016
DOI: 10.1158/0008-5472.can-15-1501
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B Deficiency Enables the Ability of a High-Fat Diet to Drive the Invasive Character of PTEN-Deficient Prostate Cancers

Abstract: Diet affects the risk and progression of prostate cancer (PCa), but the interplay between diet and genetic alterations in this disease is not understood. Here we present genetic evidence in the mouse showing that PCa progression driven by loss of the tumor suppressor Pten is mainly unresponsive to a high fat diet (HFD), but that coordinate loss of the protein tyrosine phosphatase Ptpn1 (PTP1B in human) enables a highly invasive disease. PCa in Pten-/-Ptpn1-/- mice was characterized by increased cell proliferat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The mechanism of HFDinduced tumor progression of prostate cancer may not only be inflammation. Changes in cholesterol in the cell membrane or a deficiency of the protein tyrosine phosphatase 1B with administration of an HFD might result in tumor progression of PTEN-deficient prostate cancer (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of HFDinduced tumor progression of prostate cancer may not only be inflammation. Changes in cholesterol in the cell membrane or a deficiency of the protein tyrosine phosphatase 1B with administration of an HFD might result in tumor progression of PTEN-deficient prostate cancer (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical effects of PTP1B in tumor progression also occurred in different prostate cancer animal models. PTP1B has been linked with a tumorpromoting function for migration and invasion in prostate cancer, which is dependent on androgen receptor signaling (Lessard et al 2012), whereas coordinated loss of PTP1B in PTEN-deficient mice caused an invasive prostate cancer upon high-fat diet feeding due to elevated PI3K-AKT signaling (Labbe et al 2016). Finally, the PRLs (phosphatase of regenerating liver) offer an intriguing example of a PTP that serves an oncogenic function through a mechanism that does not involve the catalytic activity of the enzyme; instead, it promotes tumor growth by forming a heterodimer with members of the CNNM family of magnesium transporters and regulating levels of intracellular magnesium (Hardy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B (DA) expression was achieved by crossing these mice to Meox2-Cre mice. Excision of the STOP cassette was assessed by live imaging as previously described ( Figure S2B) (47). Two weeks post TAC, Flag-PTP1B immunoprecipitation from heart lysates validated PTP1B (DA) expression in Rosa26 PTPN1-DA/WT mice compared to Rosa26 WT/WT control littermates and revealed that AGO2 was a substrate of PTP1B in vivo ( Figure 5B).…”
Section: Ago2 Is a Substrate Of Ptp1b In Cardiomyocytes And In Heartsmentioning
confidence: 89%